Pretreatment for water reuse using fluidized bed crystallization. (June 2020) - AzadiAghdam, Mojtaba; Park, Minkyu; Lopez-Prieto, Israel J.; Achilli, Andrea; Snyder, Shane A.; Farrell, James
Graphical abstract: Highlights: Up to 99.9 % of Mg 2+, 97 % of Ca 2+ and 42 % of silica removed. NOM removal via co-precipitation with Mg(OH)2 . All five NOM components showed some removal. Up to 100 % autochthonous fulvic acids removed. Abstract: This research investigated the use of fluidized bed crystallization for removing scale forming species and natural organic matter (NOM) from treated municipal wastewater prior to water reclamation. The effect of pH on Ca 2+, Mg 2+, silica and NOM removal in a fluidized bed crystallization reactor (FBCR) was determined. NOM removal in the FBCR was compared to that for the conventional treatments, ultrafiltration and ferric chloride coagulation/flocculation. Under optimized conditions, fluidized bed crystallization was able to remove more than 99.9 % of Mg 2+, 97 % of Ca 2+ and 42 % of silica. The FBCR was also able to remove 25 % of NOM, which was intermediate between NOM removal by ferric chloride (56 %) and ultrafiltration (13 %). Size exclusion chromatography-organic carbon detection (SEC−OCD) indicated that the majority of NOM removal occurred via co-precipitation with Mg(OH)2 . Excitation emission matrix-parallel factor (EEM-PARAFAC) analysis was used to investigate the types of NOM removed. The FBCR was able to remove all five NOM components (three humic acids, one fulvic acid and one protein-like substance), including 100 % of the autochthonous fulvic acids. Ferric chloride was also able to remove all five NOM components, but only one third of the autochthonous fulvic acids, while ultrafiltration was able to remove only 11 % of the protein-like NOM.